If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 102 + -6 Reorder the terms: 12 + 3x = 102 + -6 Combine like terms: 102 + -6 = 96 12 + 3x = 96 Solving 12 + 3x = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 96 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 96 + -12 3x = 96 + -12 Combine like terms: 96 + -12 = 84 3x = 84 Divide each side by '3'. x = 28 Simplifying x = 28
| 2+(4.5)= | | 6x+3-8x=-21 | | 5p+5t= | | 5(y+2)=3y-4+y | | (6-2x)(-5)= | | 4B-32B=36B-8BY | | 6x-2-x=13 | | 11x+19=5x+1 | | 116-4x=32x+24 | | 24x^2+17x+3=0 | | 2(3y-5x)= | | x^20= | | 4x-5=2x+8 | | -2+18d=19d+10 | | -6a(a+3)= | | 5n-2=-2n+1 | | 4r-8r+8+r= | | 36-6y=18x-6 | | x^2+10+23=0 | | -18+54X=27 | | 14x^2+17x-6= | | Y=[[x+5]] | | 8(b-3)= | | 5x+2xw=7-4xy | | -3(2x-4)=8x | | -6(3+x)=-24 | | 15-5t=55 | | 60R-90R=70 | | 166-6x=6x | | 5-(3+t)=-1+2(-3+t) | | 4x^2-2x-16=0 | | x(6-1)-2=13 |